2019
DOI: 10.1186/s43055-019-0032-9
|View full text |Cite
|
Sign up to set email alerts
|

Automated breast ultrasound (ABUS) as a screening tool: initial experience

Abstract: Background Breast cancer is a major health problem, being the most common cancer in women. Early detection of breast cancer aims to the reduction of mortality and morbidity rates. Conventional screening methods include mammography and ultrasonography; however, both modalities have their limitations. Automated breast ultrasound (ABUS) is a recent technological advancement in the field of breast imaging having the benefit of standardization of the scans and lack of operator dependence as in conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…BUS has the potential to be utilized as mammography’s adjunct [ 5 ]. A BUS’s improvement is the automated BUS ( ABUS ), having the ability in decreasing operator’s dependence when compared to conventional handheld ultrasound scans [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…BUS has the potential to be utilized as mammography’s adjunct [ 5 ]. A BUS’s improvement is the automated BUS ( ABUS ), having the ability in decreasing operator’s dependence when compared to conventional handheld ultrasound scans [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of breast cancer aims to reduce morbidity and mortality rates. Mammography has been established as the imaging modality for screening and early detection of breast cancer; however, it is accused of having low sensitivity and specificity in women with dense breasts [1].…”
Section: Introductionmentioning
confidence: 99%
“…Automated breast ultrasound (ABUS) may be used instead of the more commonly applied hand-held ultrasound (HHUS) allowing a standardization of the image acquisition, complete coverage of the whole breast volume, and the delegation of the acquisition task to the technician [ 16 , 17 ]. In first clinical studies, ABUS demonstrated similar accuracy as hand-held ultrasound; moreover, ABUS increased the cancer detection rate in combination with conventional mammography [ 18 , 19 ]. One of the disadvantages of ABUS examinations is the large number of images resulting in an increased reading time for inexperienced radiologists.…”
Section: Introductionmentioning
confidence: 99%